2020
DOI: 10.3389/fpls.2020.611897
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid:Diacylglycerol Acyltransferase1 Overexpression Delays Senescence and Enhances Post-heat and Cold Exposure Fitness

Abstract: In an alternative pathway to acyl-CoA: diacylglycerol acyltransferase (DGAT)-mediated triacylglycerol (TAG) synthesis from diacylglycerol, phospholipid:diacylglycerol acyltransferase (PDAT) utilizes not acyl-CoA but an acyl group from sn-2 position of a phospholipid, to form TAG. The enzyme’s activity in vitro matches DGAT’s in a number of plant species, however its main function in plants (especially in vegetative tissue) is debatable. In the presented study, we cultivated PDAT1-overexpressing, pdat1 knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
(55 reference statements)
4
18
1
Order By: Relevance
“…Regarding high temperature, when olive fruit was incubated at 35°C the transcript levels of the three olive PDAT genes remained almost unaffected ( Figure 7B ). Interestingly, it has been recently reported that heat stress stimulates AtPDAT1 expression in rosettes of Arabidopsis seedlings ( Demski et al, 2020 ). Furthermore, AtPDAT1-mediated TAG accumulation in Arabidopsis seedlings has been found to increase heat resistance and augments basal thermotolerance ( Mueller et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding high temperature, when olive fruit was incubated at 35°C the transcript levels of the three olive PDAT genes remained almost unaffected ( Figure 7B ). Interestingly, it has been recently reported that heat stress stimulates AtPDAT1 expression in rosettes of Arabidopsis seedlings ( Demski et al, 2020 ). Furthermore, AtPDAT1-mediated TAG accumulation in Arabidopsis seedlings has been found to increase heat resistance and augments basal thermotolerance ( Mueller et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies also revealed a critical physiological role for AtPDAT1-mediated TAG synthesis in the protection against fatty acid-induced cell death in growing tissues ( Fan et al, 2013b ), and in the process of diverting fatty acids from membrane lipids toward β-oxidation, thereby maintaining membrane lipid homeostasis in Arabidopsis leaves ( Fan et al, 2014 ). In the same tissue, it has also been reported that AtPDAT1 could be involved in stress responses ( Fan et al, 2017 ; Mueller et al, 2017 ; Demski et al, 2020 ), although the role of PDAT in plant responses to different stresses remains to be completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Data on C. sativa are still missing. Our results concerning the fatty acid composition of acyl-lipids in C. sativa leaves show that this plant possesses a similar composition of fatty acids to A. thaliana , both when plants are cultured in in vivo [ 16 , 34 , 35 ] and in in vitro conditions [ 31 ]. The composition of individual lipid classes in leaves from in vivo conditions also seems to be comparable to that of A. thaliana [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies in the field of lipid biochemistry have also been conducted based on the use of in vitro cultures. Most of them concern the determination of the activity of enzymes related to lipid biosynthesis, mainly focusing on the comparison of wild lines and genetically modified ones or testing the impact of diverse abiotic stresses [28][29][30][31]. These studies often do not take into account the effect of the introduced modifications on plants grown under standard conditions (in vivo), which might be completely different, such as in the case of secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures affect the lipid composition and viscosity of the membrane, the hotter temperature made more fluid cell membranes. This phenomenon is attributed to the activation of the accumulation and remodeling of the lipid composition of the membrane (Figure 4) [35,36].…”
Section: Regulation Of Lipid Biosynthesismentioning
confidence: 99%